2012
DOI: 10.1088/0957-4484/23/16/165702
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric–carbon nanotube memory devices

Abstract: One-dimensional ferroelectric nanostructures, carbon nanotubes (CNT) and CNT-inorganic oxides have recently been studied due to their potential applications for microelectronics. Here, we report coating of a registered array of aligned multi-wall carbon nanotubes (MWCNT) grown on silicon substrates by functional ferroelectric Pb(Zr,Ti)O3 (PZT) which produces structures suitable for commercial prototype memories. Microstructural analysis reveals the crystalline nature of PZT with small nanocrystals aligned in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It is of recent interest to fabricate functional ferroelectrics as end units onto both carbon nanotubes and graphene sheets [291][292][293][294][295]. The latter can serve as an FET gate, replacing the conventional Si/SiO 2 (see "carbon-ferroelectric gates") [296].…”
Section: Combinations With Graphene and With Carbon Nanotubesmentioning
confidence: 99%
“…It is of recent interest to fabricate functional ferroelectrics as end units onto both carbon nanotubes and graphene sheets [291][292][293][294][295]. The latter can serve as an FET gate, replacing the conventional Si/SiO 2 (see "carbon-ferroelectric gates") [296].…”
Section: Combinations With Graphene and With Carbon Nanotubesmentioning
confidence: 99%
“…In addition, the other competitors for the next generation of computer memories all have their own problems: ferroelectric nanotubes [7][8][9][10][11][12][13][14][15][16] are mechanically not very robust nor easy to manufacture with high yields; phase-change memories 17 have a small operating temperature range unsuited for either military or automotive specifications and too large a thermal budget; however, Samsung has had a 512-Mb phase-change random access memory (PRAM) in production since 2006. MRAMs 18 have problems with cross-talk if not isolated bit-by-bit with space-demanding pass-gate transistors, which are undesirable with respect to cost and 'footprint' size on the chips; however, MRAMs are also good commercial memories with Everspin producing a 4-Mb part.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, in the last years only a few reports on the investigation of multiwall carbon nanotubes (MWCNT) covered with ferroelectrics for 3D capacitors and related applications have been published. 4,5,[8][9][10] The use of MWCNT for this application is limited by the requirement to process ferroelectrics at high temperatures (> 600 ºC) in oxidizing atmospheres which results in an exothermic reaction. From our previous studies on the thermal stability of MWCNT in different atmospheres, we have demonstrated that MWCNTs are stable up to 420 o C in air but in higher P(O 2 ), they oxidise at ≥ 200 o C. However, in low P(O 2 ) (flowing Ar gas) MWCNTs can remain stable up to 1300 o C with minimum sublimation 11 .…”
Section: Introductionmentioning
confidence: 99%